Handgrip strength and physical activity in frail elderly - Maria Helena Lenardt; Maria Angélica Binotto; Nathalia Hammerschmidt Kolb Carneiro; Clovis Cechinel; Susanne Elero Betiolli; Tânia Maria Lourenço (SciELO, 2016)
Abstract OBJECTIVE To investigate the association between handgrip strength (HS) and physical activity in physical frailty elderly. METHOD Cross-sectional quantitative study with a sample of 203 elderly calculated based on the population estimated proportion. Tests were applied to detect cognitive impairment and assessment of physical frailty. Descriptive statistics and multivariate analysis by binary logistic regression were used, and also Student's t-test and Fisher's exact test. RESULTS A total of 99 (64.3%) elderly showed decreased handgrip strength and 90 (58.4%) elderly presented decrease in physical activity levels. There was a statistically significant difference between these two components (p=0.019), in which elderly who have decreased HS have lower levels of physical activity. For low levels of physical activity and decreased HS, there was no evidence of significant difference in the probability of the classification as frail elderly (p<0.001). CONCLUSION The components handgrip strength and physical activity are associated with the frail elderly. The joint presence of low levels of physical activity and decreased handgrip strength leads to a significantly higher probability of the elderly to be categorized as frailty.